2013
DOI: 10.1177/1545968313491007
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective, Neuroplastic, and Neurobehavioral Effects of Daily Treatment With Levetiracetam in Experimental Traumatic Brain Injury

Abstract: These results suggest that daily LEV treatment has beneficial effects on histological, molecular, and behavioral elements of neurological recovery after TBI, in part, via modulation of neuroinflammatory and excitatory pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…To offer more detail, LEV has recently been shown to be neuroprotective in a rodent model of controlled cortical impact (CCI) and subarachnoid hemorrhage (effect that has not been observed with PHT); administration of LEV but not PHT improved functional outcomes 34. Another rodent study showed that 20 days of LEV treatment following CCI, when compared with placebo, promoted neuronal sparing, decreased the volume of injury, and reduced release of pro-inflammatory interleukin (IL)-1β 35. Finally, LEV alone or in combination with diazepam decreased seizure-related hippocampal neurodegeneration 36.…”
Section: Seizure and Epilepsy Prevention After Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…To offer more detail, LEV has recently been shown to be neuroprotective in a rodent model of controlled cortical impact (CCI) and subarachnoid hemorrhage (effect that has not been observed with PHT); administration of LEV but not PHT improved functional outcomes 34. Another rodent study showed that 20 days of LEV treatment following CCI, when compared with placebo, promoted neuronal sparing, decreased the volume of injury, and reduced release of pro-inflammatory interleukin (IL)-1β 35. Finally, LEV alone or in combination with diazepam decreased seizure-related hippocampal neurodegeneration 36.…”
Section: Seizure and Epilepsy Prevention After Tbimentioning
confidence: 99%
“…Animal studies indicate that brain trauma causes global, in addition to focal, abnormalities, and that these abnormalities are most pronounced in the most vulnerable areas – ie, hippocampus 49. Further, animal model research has documented the relationship between TBI and seizures5052 and the positive impact of seizure medication treatments on improving neurobehavioral outcomes in TBI 35,53. Recently, human studies have shown that seizures in patients with TBI disproportionately contribute to hippocampal atrophy,54 that seizures cause increases in intracranial pressure and increased lactate/pyruvate ratio, both of which have deleterious effects on post-TBI recovery,55,56 and that patients with seizures related to any type of brain injury, when compared with matched patients without injury, have poorer outcomes and higher mortality 5760.…”
Section: Seizure and Epilepsy Prevention After Tbimentioning
confidence: 99%
“…LEV was found to act through the inhibition of the synaptic vesicle protein 2A [43], but also the inhibition of HVA-Ca 2+ channels (N-type). Moreover, it can negate the inhibition of negative allosteric modulators, such as zinc and β-carbolines of γ-aminobutyric acid (GABA)-and glycine-gated currents, and diminish the calcium release from intraneuronal stores [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…SV2A appears to be important for the availability of calcium dependent neurotransmitter vesicles ready to release their content [8]. Numerous studies have suggested that levetiracetam has considerable neuroprotective properties in both epileptic and nonepileptic disorders [9][10][11][12][13]. Its neuroprotection was demonstrated in several brain injury as well as neurodegenerative disease prototypes.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown a high affinity for synaptic vesicle protein 2A, a molecule involved in the release of neurotransmitters [35]. Zou et al [36] suggested that daily LEV treatment has beneficial effects on improvement of neurological recovery after TBI, via modulation of neuroinflammatory and excitatory pathways. Moreover, its dosage is between 1000-3000 mg, with a half-life between 6-8 hours, with minimal drug-drug interactions [37].…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%